Synthesis, Characterization, and Metal Adsorption Properties of Formaldehyde-Based Terpolymeric Resins Derived from Anthranilic Acid, Salicylic Acid, and Catechol - S. Arasaretnam; U. P. Dilshani Jayarathna (Journal of Chemistry)
Two formaldehyde-based terpolymeric resins (anthranilic acid-catechol-formaldehyde (ACF) and salicylic acid-catechol-formaldehyde (SCF)) have been synthesized by condensing anthranilic acid with catechol and salicylic acid with catechol at 80 ± 5°C using dimethylformamide as a solvent. The resins were characterized by spectral analysis using Fourier-transform infrared (FTIR) spectroscopy. The physical-chemical properties of the resins have been studied. The exchange behavior of various metal ions, namely, Cd2+, Cr3+, Ca2+, and Mg2+, towards the synthesized resins has been studied depending on contact time and pH. Chelating properties of two resins were pH dependent, and with an increase in pH value from 1 to 5, the exchange capacity of metal ions was increased. The increasing rate of ion-exchange capacity was greater in ACF than that in SCF. Cd2+ showed higher rate of exchange at different time intervals in both cases, ACF and SCF. Cr3+ had higher exchange capacity with pH variation in both resins.